Evaluation Of A Real Life Desire-to-drink Scale - Capitán Jiménez, Catalina (2016)
PURPOSE:to determine the strength of the association between the amount of fluid people say they want to drink after exercise and the actual amount of fluid intake within 30 min post-exercise.